2016
DOI: 10.1093/mnras/stw766
|View full text |Cite
|
Sign up to set email alerts
|

Roche tomography of cataclysmic variables – VII. The long-term magnetic activity of AE Aqr

Abstract: We present a long-term study of the secondary star in the cataclysmic variable AE Aqr, using Roche tomography to indirectly image starspots on the stellar surface spanning 8 years of observations. The 7 maps show an abundance of spot features at both high and low latitudes. We find that all maps have at least one large high-latitude spot region, and we discuss its complex evolution between maps, as well as its compatibility with current dynamo theories. Furthermore, we see the apparent growth in fractional spo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
(90 reference statements)
0
9
1
Order By: Relevance
“…The cause of these low states is currently suspected to be star spots passing over the L1 point on the surface of the companion star, temporarily halting mass transfer (Livio & Pringle 1994). This effect has been explored in detail in the system AE Aqr, where it was found that starspots tended to migrate and cluster around the L1 point, causing the observed low states (Hill et al 2014;Hill et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The cause of these low states is currently suspected to be star spots passing over the L1 point on the surface of the companion star, temporarily halting mass transfer (Livio & Pringle 1994). This effect has been explored in detail in the system AE Aqr, where it was found that starspots tended to migrate and cluster around the L1 point, causing the observed low states (Hill et al 2014;Hill et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its binary nature was discovered by Joy (1954). In the system, a spotted K‐type dwarf (K0‐K4 IV/V star) transfers material through the inner Lagrangian point L 1 toward a magnetic white dwarf (Hill et al 2016; Skidmore et al 2003). It has a relatively long (for a CV) orbital period of 9.88 hr (e.g., Casares et al 1996) and a very short spin period of the white dwarf of only 33 s, detected in the optical and X‐ray bands (Patterson et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Such narrow features may be artefacts due to flaring, phase-undersampling, or may be a result of the 'mirroring' effect (that acts to smear features in the latitudinal direction, see . However, given that these features are reproduced independently in both nights' maps, and given that features with a similar morphology have also been found in AE Aqr (where there was very dense phase sampling; Hill et al 2016), we interpret these as groups of starspots that have been smeared together in the reconstruction. Most prominently on the leading-inner hemisphere of SS Cyg, we find a large region affected by irradiation, as is also prominently seen in IP Peg (Watson et al 2003) and RU Peg (Dunford et al 2012).…”
Section: Surface Mapsmentioning
confidence: 66%
“…Analogous to Doppler imaging, this technique is specifically designed to indirectly image the secondary stars in close binaries such as CVs, and has been successfully applied to many systems over the past 20 years (e.g. Rutten & Dhillon 1994;Schwope et al 2004;Watson et al 2003Watson et al , 2006Watson et al , 2007Dunford et al 2012;Hill et al 2014Hill et al , 2016Parsons et al 2016). The technique assumes that the secondary is locked in synchronous rotation with a circularized orbit, and that the star is Roche-lobe filling.…”
Section: Roche Tomographymentioning
confidence: 99%